GDP OF THE G7 AFTER THE FINANCIAL CRISIS - Svitlana Radziyevska (Baltic Journal of Economic Studies)
GDP and GDP per capita as economic barometers gauge the scale of a nation’s economy and the living standards of its people. The objective of the paper is to examine the dynamics of the GDP and the GDP per capita of the G7 nations after the financial crisis of 2008-2009. Methodology. The data, taken from the official sites of the United Nations Conference on Trade and Development (UNCTAD), the International Monetary Fund (IMF), the World Bank, the United Nations, as well as monographs, articles, etc. served as the information source for using various methods, including those of experts’ assessments, comparative, graphic analysis, etc. The results demonstrate the strengthening of the US and the unstable growth of the other six members of the G7 during 2010-2023: according to the UNCTAD, the US share of the G7 rose from 45,97% to 58,52%; the US share of the world grew by 3,02%; in terms of nominal GDP, the increase was uneven across the G7: the US GDP climbed by 81,54%, or $12’284 bln; while that of Germany – by 30,75%, or $1’049 bln; Italy – by 4,92%, or $105 bln; Japan’s GDP dropped by 23,79%, or $1’307 bln. In 2023, compared to 2022, GDP per capita increased: in the US by $4’723; in France – by $4’023; in Germany – by $3’863; in Italy – by $3’544; in the UK – by $3’412; nevertheless, GDP per capita fell in Canada by $1’309 and in Japan – by $214. In 2023, according to the IMF, all the G7 members are in the top ten countries in terms of nominal GDP; and five out of seven (except Canada and Italy) are in the top ten by GDP based on PPP. The G7 share of the global economy fell from 50.09% to 43.78% between 2010 and 2022. According to the World Bank, in terms of GDP based on PPP, in 2023 the US ranked second, Japan – fifth, Germany – sixth, France – ninth, the UK – tenth, Italy – eleventh, Canada – sixteenth. According to the United Nations, India ranked first in terms of GDP growth (8.2%), followed by China (5.2%); the US and Brazil ranked third (2.9%) while the eurozone’s GDP growth rate was merely 0.4%. Practical implications. The contradictory course of globalization will push nations towards self-sufficiency, as well as cooperation with others on the regional level in order to survive amid turbulence. The leaders, as well as the leaders-to-be are expected not only to cooperate with each other, but also to take more responsibility for the future of the global world. Value/originality. It is essential to take into account the balance of power in the global space, to analyze various combinations of relations between states and groups, as well as states within groups to ensure the sustainable development of all the countries involved.